The Construction of Family Law in the Compilation of Islamic Law in Indonesia: A Review of John Rawls’s Concept of Justice and Jasser Auda’s Maqashid al-Shari'a - Nur Solikin; Moh. Wasik (Ulumuna, 2023)
Justice has long been studied by philosophers, religious figures, and politicians. It is nearly impossible to speak about the law without talking about justice since justice is the goal of the law. Rawls's concept of justice has an orientation towards social welfare (li al-maslahat al-umma). This conception has relevance to the principles of maqasid al-shari'a, which also emphasizes justice. This paper will explore Rawls’s concept of justice and Auda’s notion of maqasid al-shari'a and apply them as an analytical device to examine the construction of family formulated in the Compilation of Islamic Law. Family constitutes the most basic unit in society, and any legal stipulation related to the family must be critically re-examined. This study argues that constructing a just family based on maqasid al-sharia will form a family that benefits the family members and society. The dimension of justice fosters and provides space for equality in the domestic household. In contrast, the maqasid al-sharia dimension serves as an external dimension within the scope of the family. This dimension forms a family construction that safeguards and protects religion, the soul, the Intellect, offspring, and property.